Peningkatan Kapasitas Pembudidaya Ikan melalui Pelatihan Penggunaan Aplikasi AQUARA sebagai Sistem Informasi Pasar dan Analisis Usaha Budidaya Ikan - Nur Budi Nugraha; Rendi; Fauzan Ishlakhuddin (Journal Of Computer Science Contributions (JUCOSCO), 2026)
Limited access to market information and inadequate business analysis skills remain major challenges faced by fish farmers in managing aquaculture enterprises effectively. This community service program aimed to enhance the capacity of fish farmers through training on the use of AQUARA (Aquaculture Market Information and Business Analysis System), a web- and mobile-based application. The program was conducted in collaboration with the Department of Fisheries and Marine Affairs of Indramayu Regency through training sessions, hands-on practice, mentoring, and evaluation using questionnaires. The training materials covered market information features, business data recording, and aquaculture business analysis. The results showed that participants were able to understand and operate the application effectively. Based on the evaluation results, 92% of participants stated that the training materials were easy to understand, 90% considered the application easy to use, 94% reported that the application features met their business needs, 96% experienced improved understanding, and 91% expressed interest in using the application continuously. The program successfully improved participants' digital literacy and their ability to utilize technology to support aquaculture business management. The integration of market information and business analysis features within the AQUARA application provides added value by supporting more effective and data-driven decision-making. Therefore, AQUARA has the potential to serve as a supporting tool for digital transformation in the aquaculture sector.